The Influence of Sales Promotion and Shopping Lifestyle on Impulsive Buying Behavior of Mr DIY in Palembang City - Manalu, Anggriani Br; Changreani, Evelyn (Journal of Business Economics and Agribusiness, 2024)
This research was conducted to analyze the influence of Sales Promotion and Shopping Lifestyle on Impulse Buying among Mr DIY consumers in Palembang City. The growth of the retail industry and changes in consumer lifestyles require a deeper understanding of the factors that influence impulse shopping behavior. This research tries to answer the problem regarding the influence of Sales Promotion and Shopping Lifestyle on the tendency to shop impulsively at stores like Mr DIY. The purpose of this research is to find out whether Sales Promotion and Shopping Lifestyle influence Impulse Buying in Mr DIY, Palembang City. This research aims to provide a clear and specific picture of the factors that influence consumers' impulsive shopping decisions. This research uses a quantitative approach with non-probability sampling techniques and a purposive sampling approach to select 100 respondents. Data analysis was carried out using statistical methods which included regression to test the influence of the Sales Promotion and Shopping Lifestyle variables on Impulse Buying. The population of this research is Mr DIY consumers in Palembang City. A sample of 100 respondents was selected purposively to achieve appropriate representation. The research results show that Sales Promotion has no significant effect on Impulse Buying, while Shopping Lifestyle has a positive effect on the impulsive shopping behavior of Mr DIY consumers in Palembang City. In this research it can be concluded that consumer shopping lifestyles influence impulsive shopping tendencies more than sales promotions. The implications of these findings can help design more effective marketing strategies. This research contributes to the understanding of consumer behavior and retail marketing strategies. Knowing that lifestyle shopping has a stronger influence can help stores like Mr DIY to devise promotional and sales strategies that better suit consumer preferences, enrich the literature on impulse shopping, and provide guidance for further research.